COMPARATIVE ANALYSIS OF WORD-FORMATION MARKINGS IN THE KAZAKH AND TURKISH NATIONAL CORPORA: APPROACHES, DIFFICULTIES AND DEVELOPMENT STRATEGIES - Pirmanova Kunsulu Kambarbekkyzy; Pirmanova Ainura Kambarbekkyzy; Tokmyrzaev Darkhan Ontalapuly (Reviews of Modern Science, 2024)
This article conducts a comparative analysis of word-formation markings in the Kazakh and Turkish national corpora. The aim of the research is to identify and describe the key approaches, complexities, and strategies in word formation used in these two languages. The study has significant scientific and practical importance as word formation plays a crucial role in the development and standardization of a language. The research methodology includes analyzing word-formation structures, using computer tools for corpus linguistics, and comparative analysis. Key results reveal differences and similarities in marking methods and word formation, contributing to an understanding of the specificities of each language. The research significantly enriches philology and corpus linguistics by enhancing knowledge of word-formation processes. The practical significance of the work lies in improving corpus marking methods and developing recommendations for linguists and developers of language resources.